THE PHENOMENON OF LANGUAGE ON STREETS BANNERS DURING RAMADAN AND EID AL FITR: SPEECH ACT STUDY - Nurlina, Wiwin Erni Siti; Riani, Riani (Journal of Pragmatics and Discourse Research, 2022)
Language is a part of the human life as a mean for communication. Related to the function of language, this paper reveals one of the phenomena of language that arises in a society as a social phenomenon. The phenomenon is in the form of utterances on street banners during the fasting period of Ramadan and the Eid al-Fitr in Yogyakarta. Those utterances are discourse forms with certain meaning and purpose which are realized in speech acts. This study uses a sociopragmatic approach to explain the purpose of utterances written on the street banners, especially speech act theory. The speech acts are seen in their locution and illocution. This study uses a descriptive qualitative method that is descriptive analysis. The step taken in this method is to describe the facts found, which are then followed by data analysis. This study found several types of speech acts that purpose to educate the public in traffic and the matter of worship during Ramadan until the Eid Al-Fitr. Those speech acts are congratulation, appeal, order, remind, and announce/inform.